2015
DOI: 10.14712/23362936.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Does Sacrococcygeal Angle Play a Role on Pilonidal Sinus Etiology?

Abstract: The predisposing factors for the development of sacrococcygeal pilonidal disease (SPD) still remain undetermined. Here, we investigate the sacrococcygeal angle as a possible predisposing factor for the development of disease. Consecutive male patients admitted to our clinic with the diagnosis of SPD were included. Sex, age and BMI matched healthy controls without SPD were enrolled to the study. The predefined sacrococcygeal angles of patients and controls were measured on lateral pelvic radiographs by a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…The abscess is formed when a folliculitis infiltrates into the subcutaneous tissue or when an ongoing foreign-body granuloma becomes infected 4. Several predisposing factors of pilonidal disease have been suggested, such as hairy body, local trauma due to long periods of sitting, poor hygiene, wounded skin and positive family history 5. Certain anatomical features of sacrococcygeal area may promote the accumulation of hairs in intergluteal sulcus, but this has yet to be proven 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abscess is formed when a folliculitis infiltrates into the subcutaneous tissue or when an ongoing foreign-body granuloma becomes infected 4. Several predisposing factors of pilonidal disease have been suggested, such as hairy body, local trauma due to long periods of sitting, poor hygiene, wounded skin and positive family history 5. Certain anatomical features of sacrococcygeal area may promote the accumulation of hairs in intergluteal sulcus, but this has yet to be proven 5.…”
Section: Discussionmentioning
confidence: 99%
“…Several predisposing factors of pilonidal disease have been suggested, such as hairy body, local trauma due to long periods of sitting, poor hygiene, wounded skin and positive family history 5. Certain anatomical features of sacrococcygeal area may promote the accumulation of hairs in intergluteal sulcus, but this has yet to be proven 5. A recent study revealed that males aged 20–24 years and girls aged 10–14 years had a higher incidence of pilonidal disease, indicating that puberty, which starts earlier in girls, is an essential factor in the development of pilonidal disease 3…”
Section: Discussionmentioning
confidence: 99%
“…Negative pressure wound care products are also associated with an increase in factors accelerating wound healing such as: wound oxygenation, angiogenesis, and blood flow, granulation tissue formation (EWMA, 2008). Relative contraindications of the negative pressure wound care products are necrotic tissue formation with eschar on in the wound, priority of debridement requirement, presence of an untreated osteomyelitis around the wound, cancer in the wound or development of a fistula towards an organ or body cavity (Cooper and Young, 2000;Eryilmaz et al, 2015). When VAC (vacuum-assisted closure) treatment used as negative pressure wound care product is compared with standard gauze dressings, it is reported that VAC treatment further reduces the depth of chronic wounds, provides a faster recovery, causes fewer infections and allows shorter hospitalization (Joseph et al, 2000;Vuerstaek et al, 2006;Mouës et al, 2007).…”
Section: Negative Pressure Wound Therapymentioning
confidence: 99%
“…However, cases where the cause is not found are also quite frequent [1][2][3]. Conservative methods such as use of donut-shaped cushions, rest, medical treatment, physical therapy, massage, radiotherapy, psychotherapy, sacral rhizotomy, manipulation, epidural injection, and local injection have been successfully applied in the treatment of coccydynia [1][2][3][4]. Coccygectomy surgery is performed in patients who do not benefit from conservative treatment methods [3,5].…”
Section: Introductionmentioning
confidence: 99%